-
If a2 = by + cz, b2 = cz + ax, c2 = ax + by, then the value of
x + y + z is a + x b + y c + z
-
- 1
- a + b + c
-
1 + 1 + 1 a b c - 0
Correct Option: A
a2 = by + cz
⇒ a2 + ax = ax + by + cz
⇒ a (a + x) = ax + by + cz
⇒ | = | ||
a + x | ax + by + cz |
Similarly,
b2 = cz + ax
⇒ b2 + by = by + cz + ax
⇒ b (b + y) = ax + by + cz
⇒ | = | ||
b + y | ax + by + cz |
c2 = ax + by
⇒ c2 + cz = ax + by + cz
⇒ c (c + z) = ax + by + cz
⇒ | = | ||
c + z | ax + by + cz |
= | + | + | |||
ax + by + cz | ax + by + cz | ax + by + cz |
= | = 1 | |
ax + by + cz |